Program conversing in Portugese providing a library service - Coelho, Helder (The University of Edinburgh, 1979)
TUGA is a program which converses in Portuguese to provide a library service covering the field of Artificial Intelligence. The objective of designing the program TUGA was the development of a feasible method for consulting and creating data bases in natural Portuguese. The resulting program allows dialogues where the program and its users behave in the way humans normally do in a dialogue setting. The program can answer/ and question in pre-defined scenarios. Users can question/ answer and issue commands in a natural and convenient way/ without bothering excessively with the form of the dialogues and sentences. The original contributions of this work are: the treatment of dialogues. the adaptation of Colmerauer's natural language framework to Portuguese, the particular method for evaluating the logical structures involved in Colmerauer's framework, and the library service application itself. The program is implemented in Prolog, a simple and surprisingly powerful programming language essentially identical in syntax and semantics to a subset of predicate calculus in clausal form.